Restoring rangelands: the art of flexible livestock management - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
A blog about the importance of the flexible grazing management strategies to meet rangeland resources sustainability targets. In Tunisia, livestock used to obtain over 80% of their feed from rangelands- today, this has fallen to 20%. Therefore and to optimize the use of rangelands, representatives from ICARDA, the Office of Livestock and Pastures (OEP), and Tunisia's General Directorate for Forestry (DGF); farmers; and pastoralists to a day-long workshop on June 6, 2022, where participants discussed a flexible approach to grazing management as proven innovation that that guarantee the sustainability of rangeland resource.